Ultrasound Differentiation of Benign and Malignant Cervical Lymph Nodes - Rahman, Md Mizanur; Sadeque, ASQM; Omar, Eliza; Khakta, Sonjoy Kumar (Ibrahim Medical College Journal, 2010)
This study was conducted to see whether the size (measured by maximal short axis diameter), shape (expressed in terms of ratio dividing long axis diameter of the node by short axis diameter or L/S ratio), marginal clarity (regular or irregular margin), internal echo-pattern (homogeneous hypoechoic or heterogeneous) and hilar echogenicity (presence or absence of echo-genicity in hilum) are good criteria for differentiating benign from malignant cervical lymph nodes using high frequency (high resolution) ultrasound probe. The study was carried out from January 1998 to December 1998, among patients with enlarged cervical lymph nodes who were scanned with a high frequency (5.0 MHz) curvilinear probe. Chi-Square test was done to see the statistical correlation between two groups of nodes. A p value of <0.05 was taken as significant. Out of 65 nodes studied, 26 (100%) enlarged cervical nodes with short axis diameter more than 1 cm were all malignant. In contrast 31 (79.5%) of 39 enlarged nodes with short axis diameter less than 1cm were benign and rest were malignant (p<0.001). Of 34 enlarged nodes with L/S ratio <2, 30 (88.2%) nodes were found malignant and 4 (11.8%) were benign. Among the rest 31 enlarged nodes, 27 (87.1%) with L/S ratio ≥ 2 were benign while 4 (12.9%) were malignant (p <0.001). Among the 39 nodes with regular margin 28 (71.8%) were found benign, where as among 26 nodes with irregular margin 23 (88.5%) were malignant (p <0.001). When the internal echopattern was taken in account, 32 nodes had homogeneous hypoechoic echo of which 28 (87.5%) were benign and among 33 nodes with heterogeneous echopattern 30 (90.9%) were malignant (p <0.001). Among the 43 enlarged nodes with presence of hilar echogenicity 31(72.1%) were found benign and 22 (100%) nodes with no hilar echogenicity were all malignant (p <0.001). Such findings suggest that real time high resolution ultrasound might assist in differentiation of benign and malignant enlarged cervical lymph nodes. Ibrahim Med. Coll. J. 2009; 3(2): 40-44 Indexing words: Ultrasound, cervical lymph nodes, benign, malignant. DOI: 10.3329/imcj.v3i2.4161